Analisis Pemilihan Tenaga Kependidikan Terbaik Menggunakan Metode Weighted Product - Ambo, Sitti Nurbaya; Mujiastuti, Rully; Susilowati, Emi (JISA(Jurnal Informatika dan Sains), 2019)
Education Personnel (Tendik) in higher education have an important role because they are tasked with carrying out administration, management, development, supervision, and technical services to support the education process in the education unit. The Tendik staff consists of administrative staff, library staff and laboratory staff. The success of Tendik in carrying out his work load can be seen from the criteria of attendance, job responsibilities, cooperation, loyalty, archiving and service. Furthermore, to be able to evaluate, motivate, and to be able to do promotion of tendik, it is necessary to make an effort in the form of selection of the best tendik, which so far has not been done in the Faculty of Engineering, University of Muhammadiyah Jakarta (FT UMJ). Recommendations for the selection of the best tendons made in this study using the Weighted Product method based on criteria established by the Quality Assurance Unit of FT UMJ. The results showed that the best selection of tendons was obtained from t e largest vector values in V3, V7, V9, V15, and V16, so that alternatives A3, A7, A9, A15, and A16 were the alternatives chosen as the best Tendik in FT UMJ. These results can be a recommendation for the leadership of FT UMJ to provide appreciation and promotion of the best Tendik as well as to evaluate, motivate and provide training for unskilled Tendik.